2002
DOI: 10.1038/sj.bjp.0704451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phencyclidine (PCP) and MK 801 on the EEGq in the prefrontal cortex of conscious rats; antagonism by clozapine, and antagonists of AMPA‐, α1‐ and 5‐HT2A‐receptors

Abstract: 1 The electroencephalographic (EEG) e ects of the propsychotic agent phencyclidine (PCP), were studied in conscious rats using power spectra (0 ± 30 Hz), from the prefrontal cortex or sensorimotor cortex. PCP (0.1 ± 3 mg kg 71 s.c.) caused a marked dose-dependent increase in EEG power in the frontal cortex at 1 ± 3 Hz with decreases in power at higher frequencies (9 ± 30 Hz). At high doses (3 mg kg 71 s.c.) the entire spectrum shifted to more positive values, indicating an increase in cortical synchronization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 89 publications
8
51
0
Order By: Relevance
“…The resulting hyperglutamatergic state is believed to mediate the enhanced field gamma activity by stimulating kainate and AMPA receptor-mediated activation of the cortical interneuron-pyramidal cell network (McNally et al, 2011;Roopun et al, 2008). Indeed, a robust increase in field gamma oscillations is one of the most consistent findings in response to systemic treatment with NMDA antagonists (Hakami et al, 2009;Kocsis, 2012;Sebban et al, 2002).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The resulting hyperglutamatergic state is believed to mediate the enhanced field gamma activity by stimulating kainate and AMPA receptor-mediated activation of the cortical interneuron-pyramidal cell network (McNally et al, 2011;Roopun et al, 2008). Indeed, a robust increase in field gamma oscillations is one of the most consistent findings in response to systemic treatment with NMDA antagonists (Hakami et al, 2009;Kocsis, 2012;Sebban et al, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…To understand whether the induced gamma is a mere reflection of the elevation in baseline gamma activity that NMDA antagonists are well known to engender (Hakami et al, 2009;Kocsis, 2012;Sebban et al, 2002), we compared induced power through duration of train stimulation with the total gamma band power at the beginning of each epoch when there was no auditory stimulation. We found a highly significant positive correlation (Pearson's r) and no statistical difference between the two measures (paired t-test; data not shown) under all treatment conditions, suggesting that induced power in our paradigm was merely reflecting the gamma power present in the signal.…”
Section: Induced Powermentioning
confidence: 99%
“…This drug increases LFP power in the delta (1-4 Hz) and theta (4-8 Hz) bands in various cortical regions, an effect blocked with FLU coadministration (Ehlers et al, 1990;Massotti, 1985;Massotti et al, 1985). Interestingly, as well as impairing working memory and burst firing in mPFC, systemic administration of NMDA receptor antagonists also increases LFP power in the delta band in this region (Sebban et al, 2002). Therefore, altered LFP activity in mPFC may represent another common mechanism by which cognitive function is perturbed.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that PCP increases extracellular levels of glutamate and dopamine in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) (1), presumably as a result of decreased activation of NMDA receptors on GABAergic interneurons. Excess glutamate activation of AMPA receptors appears to be involved in the effects of PCP because an AMPA antagonist blocks the behavioral effects of PCP in animal models (2)(3)(4)(5). As a result, the glutamate theory of schizophrenia supports the development of drugs that reduce PCP-induced glutamate release as novel antipsychotic therapies.…”
mentioning
confidence: 92%